2021
DOI: 10.1038/s41598-021-91747-6
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic nucleoside phosphonates with adenine nucleobase inhibit Trypanosoma brucei adenine phosphoribosyltransferase in vitro

Abstract: All medically important unicellular protozoans cannot synthesize purines de novo and they entirely rely on the purine salvage pathway (PSP) for their nucleotide generation. Therefore, purine derivatives have been considered as a promising source of anti-parasitic compounds since they can act as inhibitors of the PSP enzymes or as toxic products upon their activation inside of the cell. Here, we characterized a Trypanosoma brucei enzyme involved in the salvage of adenine, the adenine phosphoribosyl transferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 51 publications
6
14
0
Order By: Relevance
“…The reduction in APRT activity is explained by the 1:1 dilution of APRT1, thereby indicating a catalytically active APRT1:APRT2 heterodimer is not formed. A recent study revealed APRT1 and APRT2 do not interact in vivo, with APRT1 displaying homodimeric properties both in vivo and in vitro [41], in agreement to results showed in Fig 3 . The quaternary structure of APRT1 was evaluated in vitro by treating APRT1 and APRT2 with DMS, an agent that chemically crosslinks two lysine residues within a monomer and also between lysine residues found in two or more associated monomers (Fig 4) [46]. Analysis of crosslinked proteins by denaturing polyacrylamide electrophoresis will show homodimers and other multimers, indicating quaternary structure, which will still be observed after significant protein dilution.…”
Section: Substratesupporting
confidence: 92%
See 4 more Smart Citations
“…The reduction in APRT activity is explained by the 1:1 dilution of APRT1, thereby indicating a catalytically active APRT1:APRT2 heterodimer is not formed. A recent study revealed APRT1 and APRT2 do not interact in vivo, with APRT1 displaying homodimeric properties both in vivo and in vitro [41], in agreement to results showed in Fig 3 . The quaternary structure of APRT1 was evaluated in vitro by treating APRT1 and APRT2 with DMS, an agent that chemically crosslinks two lysine residues within a monomer and also between lysine residues found in two or more associated monomers (Fig 4) [46]. Analysis of crosslinked proteins by denaturing polyacrylamide electrophoresis will show homodimers and other multimers, indicating quaternary structure, which will still be observed after significant protein dilution.…”
Section: Substratesupporting
confidence: 92%
“…When the same RNAi cell line was tested as bloodstream stage cells grown in medium containing adenine as the sole available purine, a significant growth phenotype was observed suggesting the APRTs are the only enzymes that can incorporate adenine into the purine salvage pathway. The same publication reported another RNAi cell line, silencing APRT1 activity only, which displayed a growth phenotype similar to the bloodstream stage cells grown in medium containing only adenine, suggesting APRT2 is not able to compensate for the loss of APRT1 even when media contained up to 50 µM adenine [41].…”
Section: Substratementioning
confidence: 96%
See 3 more Smart Citations